2011
DOI: 10.1007/s11605-011-1621-8
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Transmural Drainage of Peripancreatic Fluid Collections: Outcomes and Predictors of Treatment Success in 211 Consecutive Patients

Abstract: Endoscopic therapy is a highly effective technique for the management of patients with non-necrotic peripancreatic fluid collections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
174
7
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(199 citation statements)
references
References 30 publications
12
174
7
6
Order By: Relevance
“…Sadik et al [48] noted a 94% success rate and 5% complication rate in simple pseudocysts vs 80% success rate and 30% complication rate in infected pseudocysts. Similarly, Varadarajulu et al [49] found a 93.5% success rate and 5% complication rate vs a 63% success rate and 16% complication rate in sterile vs infected pseudocysts. This suggests that while EUS guided drainage is still efficacious, infected pseudocysts are more difficult to drain and associated with a higher complication rate.…”
Section: Percutaneous Drainagementioning
confidence: 89%
“…Sadik et al [48] noted a 94% success rate and 5% complication rate in simple pseudocysts vs 80% success rate and 30% complication rate in infected pseudocysts. Similarly, Varadarajulu et al [49] found a 93.5% success rate and 5% complication rate vs a 63% success rate and 16% complication rate in sterile vs infected pseudocysts. This suggests that while EUS guided drainage is still efficacious, infected pseudocysts are more difficult to drain and associated with a higher complication rate.…”
Section: Percutaneous Drainagementioning
confidence: 89%
“…With expertise PFCs that have failed drainage by other methods and those in unusual locations are also considered for drainage [7,16,23] . Many experts recommend assessment of the main pancreatic duct at the time of PFC drainage with ERCP as uniden- tified pancreatic duct stricture or leak may result in failure of resolution or recurrence of PFC [16,24,25] .…”
Section: Prerequisites For Eus Drainagementioning
confidence: 99%
“…Grimm et al [31] , 1992 (1) Retrospective 100 100 0 Nil Binmoeller et al [21] , 1995 (27) Retrospective 93 78 7 Bleeding (n = 2) Giovannini et al [32] , 2001 (35) Prospective 100 89 3 Pneumoperitoneum (n = 1) Azar et al [33] , 2006 (23) Retrospective 91 82 4 Pneumoperitoneum (n = 1) Antillon et al [19] , 2006 (33) Prospective 94 87 15 Bleeding (n = 4), pneumoperitoneum (n = 1) Krüger et al [34] , [35] , 2006 (46) Prospective 100 93.5 20 Superinfection (n = 4), bleeding (n = 2), pneumoperitoneum (n = 2) stent migration (n = 1) Hookey et al [22] , 2006 (32) Retrospective 96 93 9 Pneumoperitoneum (n = 2), bleeding (n = 1) Lopes et al [36] , 2007 (51) Retrospective 94 84 4 Pneumoperitoneum (n = 1), migration (n = 1) Varadarajulu et al [37] , 2007 (21) Prospective 100 95 0 None Barthet et al [38] , 2008 (28) Prospective 100 89 18 Superinfection (n = 5) Varadarajulu et al [39] , 2008 (24) Randomized controlled trial 100 96 0 Nil…”
Section: Complicationsmentioning
confidence: 99%
“…Clinical success rates of 70% to 87% have been reported in multiple studies, with complication rates of 11% to 34%. 30,[33][34][35] Drainage of more complex collections (acute necrotic collections [ANC], WOPN) can also be achieved surgically, via the percutaneous route, as well as endoscopically. There is controversy in the approach to these complex types of PFCs containing variable amounts of necrotic debris and this is reflected in the most recent consensus guidance from the International Association of Pancreatology (IAP) and the American Pancreatic Association (APA).…”
Section: Eus-guided Transmural Drainage Of Pfcsmentioning
confidence: 99%
“…39 Recent studies have shown that while endoscopic EUS-guided drainage of pseudocysts is highly successful and safe, drainage of necrotic collections is technically more challenging and carries higher risks. 35,40 This suggests that while EUS-guided puncture of a complex PFC-containing solid necrotic material is still technically feasible, some concerns arise as to the effectiveness of draining of the cyst contents through the cyst gastrostomy or cyst-duodenostomy fistulous tract. 41 Some of the inherent risks of the endoscopic approach include the risk of air embolism, endoscopically uncontrollable bleeding and inadequate drainage through multiple plastic stents, as well as early occlusion of the fistulous tract.…”
mentioning
confidence: 99%